Exploring parents’ experiences of palliative care in the pediatric intensive care unit (PICU): a meta-synthesis of qualitative research - Zheng Jiang; Li Wang; Xuehua He; Qiqi Ni; Yewan Zhan; Liqing Chen; Qian Chen; Yijing Weng; Yiyu Zhuang (BMC Nursing, 2026)
Abstract Background When the goals of care for a critically ill child in the pediatric intensive care unit (PICU) shift from curative treatment toward palliative care, parents’ experiences are often complex and multifaceted. This review aimed primarily to synthesize qualitative evidence on parents’ experiences and, secondarily, to examine the interpretive relevance and boundaries of Weick’s sensemaking framework after the data-driven synthesis had been completed. Methods We conducted a qualitative systematic review using the Joanna Briggs Institute (JBI) meta-aggregation approach. PubMed, Embase, CINAHL, Web of Science, the Cochrane Library, and ProQuest were searched from inception to 2 February 2026. Two reviewers independently screened studies, extracted author-generated analytical findings and supporting participant illustrations, and appraised methodological quality. Findings were synthesized inductively; the 15 resulting subdomains were subsequently mapped to Weick’s seven properties of sensemaking. Results Ten studies were included. Meta-aggregation generated five interrelated synthesized findings: (1) confronting and understanding the end-of-life reality; (2) finding recognition and support through relational networks; (3) maintaining the parental role; (4) safeguarding comfort, dignity, and farewell; and (5) continuing care and connection after the child’s death. Conclusions Parents’ experiences encompassed efforts to understand a changing clinical situation, rely on relationships with clinicians and others, remain involved as parents, protect the child’s comfort and dignity, and sustain connection after death. Weick’s framework helped interpret how parents used clinical cues, relationships, identity, and caregiving actions to construct a workable understanding of events, but gave less attention to grief-related emotions, surrogate decision-making burden, cultural and spiritual meaning, organizational constraints, and continuing bonds. The findings may inform family-centered communication, parental-role support, individualized end-of-life care, and bereavement services in the PICU.